Potential Targeting of Renal Fibrosis in Diabetic Kidney Disease Using MicroRNAs - Sakuma, Hiroko; Hagiwara, Shinji; Kantharidis, Phillip; Gohda, Tomohito; Suzuki, Yusuke (Frontiers in Pharmacology, 2020)
Diabetic kidney disease (DKD) is a major health problem and one of the leading causes of end-stage renal disease worldwide. Despite recent advances, there exists an urgent need for the development of new treatments for DKD. DKD is characterized by the excessive synthesis and deposition of extracellular matrix proteins in glomeruli and the tubulointerstitium, ultimately leading to glomerulosclerosis as well as interstitial fibrosis. Renal fibrosis is the final common pathway at the histological level leading to an end-stage renal failure. In fact, activation of the Nrf2 pathway by bardoxolone methyl and inhibition of transforming growth factor beta signaling by pirfenidone have been assumed to be effective therapeutic targets for DKD, and various basic and clinical studies are currently ongoing. MicroRNAs (miRNAs) are endogenously produced small RNA molecules of 18–22 nucleotides in length, which act as posttranscriptional repressors of gene expression. Studies have demonstrated that several miRNAs contribute to renal fibrosis. In this review, we outline the potential of using miRNAs as an antifibrosis treatment strategy and discuss their clinical application in DKD.